Comparative study between laser and conventional techniques for class V cavity preparation in gamma-irradiated teeth (in vitro study) - Amr H. M. Rasmy; Tarek A. Harhash; Rami M. S. Ghali; Eman M. F. El Maghraby; Dalia H. El Rouby
Abstract Objective: The purpose of this study was to compare laser with conventional techniques in class V cavity preparation in gamma-irradiated teeth. Methods: Forty extracted human teeth with no carious lesions were used for this study and were divided into two main groups: Group I (n = 20) was not subjected to gamma radiation (control) and Group II (n=20) was subjected to gamma radiation of 60 Gray. Standard class V preparation was performed in buccal and lingual sides of each tooth in both groups. Buccal surfaces were prepared by the Er,Cr:YSGG laser (Waterlase iPlus) 2780 nm, using the gold handpiece with MZ10 Tip in non-contact and the "H" mode, following parameters of cavity preparation - power 6 W, frequency 50 Hz, 90% water and 70% air, then shifting to surface treatment laser parameters - power 4.5 W, frequency 50 Hz, 80% water and 50% air. Lingual surfaces were prepared by the conventional high-speed turbine using round diamond bur. Teeth were then sectioned mesio-distally, resulting in 80 specimens: 40 of which were buccal laser-treated (20 control and 20 gamma-irradiated specimens) and 40 were lingual conventional high-speed bur specimens (20 control and 20 gamma-irradiated specimens). Results: Microleakage analysis revealed higher scores in both gamma groups compared with control groups. Chi-square test revealed no significant difference between both control groups and gamma groups (p=1, 0.819, respectively). A significant difference was revealed between all 4 groups (p=0.00018). Conclusion: Both laser and conventional high-speed turbine bur show good bond strength in control (non-gamma) group, while microleakage is evident in gamma group, indicating that gamma radiation had a dramatic negative effect on the bond strength in both laser and bur-treated teeth.